Astrocyte Senescence and Alzheimer’s Disease: A Review - Han, Xiaojuan; Zhang, Tianying; Liu, Huanhuan; Mi, Yajing; Gou, Xingchun (Frontiers in Aging Neuroscience, 2020)
Astrocytes are the largest group of glial cells in the brain and participate in several essential functions of the central nervous system (CNS). Disruption of their normal physiological function can lead to metabolism disequilibrium and the pathology of CNS. As an important mechanism of aging, cellular senescence has been considered as a primary inducing factor of age-associated neurodegenerative disorders. Senescent astrocytes showed decreased normal physiological function and increased secretion of senescence-associated secretory phenotype (SASP) factors, which contribute to Aβ accumulation, tau hyperphosphorylation, and the deposition of neurofibrillary tangles (NFTs) in Alzheimer’s disease (AD). Astrocyte senescence also leads to a number of detrimental effects, including induced glutamate excitotoxicity, impaired synaptic plasticity, neural stem cell loss, and blood–brain barrier (BBB) dysfunction. In this review article, we have summarized the growing findings regarding astrocyte senescence and its putative role in the pathologic progress of AD. Additionally, we also focus on the significance of targeting astrocyte senescence as a novel and feasible therapeutic approach for AD.